Change in Police Attendance at Overdose Events following Implementation of a Police Non-Notification Policy in British Columbia. (10th October 2022) - Mehta, Amiti; Xavier, Jessica C.; Palis, Heather; Slaunwhite, Amanda; Jenneson, Sandra; Buxton, Jane A.
Abstract : Introduction . Bystanders at overdose events often hesitate to call 911 due to fear of police involvement. To address this, in 2016, British Columbia Emergency Health Services (BCEHS) introduced a policy to not routinely inform police of overdose events. This study explores change in police attended overdose events after the policy was implemented. Methods . Data on police attended overdose events were derived from naloxone administration forms in BC's Take-Home Naloxone (THN) kits returned before and after the policy change. Segmented regression was conducted to quantify change in police attended overdose events. Results . The average proportion of police attended overdose events pre-policy was 55.6% compared to 37.9% post-policy. The segmented regression model demonstrated a 0.98% (95% CI: (−1.70 to −0.26)) decline (p = 0.01 ) in police attended overdose events each month following the policy. Conclusion . Our findings suggest that the BCEHS policy contributed to a decrease in police attended overdose events.